(untitled) (International Conference on Computers in Education, 2013)
21st century education has to be self-generating and self-sustaining, freely accessible to anyone, anytime, anywhere, and characterized by collaborative, two-way applied acquisition and mastery of productive and metacog nitive knowledge, skills, and attitudes. As a medium of delivery, a digital entertainment game requires an integrated continuum of achievable roles including consumer, producer, and manager of content and activities in gameplay, community, management, and development. This paper identifies a variety of digital entertainment games which demonstrate some of these features, evaluates their potential value using our Game Regulated Applied Integrated Learning model, and discusses implications for selection and design of game systems intended for education.